Reply to ’Pancreatic Metastasis from Colon Carcinoma Treated with Radiotherapy with Palliative Benefit’ - Machado, Norman Oneil (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Sultan Qaboos University Hospital. Muscat, Oman.